Question Number 114134 by sherzodbek last updated on 17/Sep/20

(m^2 −n^2 +6(n+m)/(m^2 −(6−n)^2   m+n=12

Commented bysherzodbek last updated on 17/Sep/20

yes

Commented bybemath last updated on 17/Sep/20

do you meant ((m^2 −n^2 +6(n+m))/(m^2 −(6−n)^2 )) ?  where m+n = 12

Commented bybemath last updated on 17/Sep/20

⇔ ((12(m−n)+72)/((m+6−n)(m+n−6))) =  ((12(m−n)+72)/((m−n+6)(6))) =((2(m−n)+12)/(m−n+6))  = ((2(12−n−n)+12)/(12−n−n+6))  = ((36−4n)/(18−2n)) = ((2(18−2n))/(18−2n)) = 2

Commented byMJS_new last updated on 17/Sep/20

((m^2 −n^2 +6(n+m))/(m^2 −(6−n)^2 ))=((m+n)/(m+n−6))=2

Answered by sherzodbek last updated on 17/Sep/20

Commented bymathmax by abdo last updated on 18/Sep/20

really good for somebody....